131 Left ventricular indexed mass associated with ventricular arrhythmias in patients with hypertrophic cardiomyopathy – a tertiary centre mri registry. (5th June 2017) - Khan, Habib; Somarakis, Konstantinos; Thain, Andrew; Al-Atta, Ayman; Mathew, Thomas
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is a common inherited cardiac condition. Multiple factors have been identified towards high risk of sudden cardiac death (SCD) as outlined in the ESC guidelines. LV wall thickness (LVwt ) is an identified risk. Left ventricular mass indexed to body surface area (LVIBSA ) increases with wall thickness and may predict risk not currently utilised in the risk score. Objectives: 1. Compare differences in LVwt using transthoracic echocardiogram(TTE) and MRI and the effect on ESC risk score. 2. Observe for association of LVIBSA and incidence of non-sustained ventricular tachycardia(NSVT) either on 24 hour holter monitor or following ICD insertion. Methods: We retrospectively reviewed patients between January 2010 to July 2015 who were confirmed to have HCM on MRI. ESC Risk was calculated using LV TTE and MRI LVwt . LVIBSA was calculated from MRI images and compared with incidence of VA on holter monitors. Patients who received ICD had follow up and VA incidence recorded. Results: 103 patients with confirmed HCM were identified with median age of 60 (range 15–87). Non sustained VT (NSVT) was recorded in 20 (19.4%) patients while 16 patients had missing or no record of holter. Primary prevention ICDs (ICD 1* ) were inserted in 20 (19.4%) patients. MRI identified a higher absolute LVwt compared to TTE in 68.9% of patients. This lead to an increase in ESC risk score from low risk to high risk in 5% of the patients (ESC score>4). LVIBSA was higher in the patients with holter positive for VA (mean 109.7g/m 2, 95% CI [92.8, 126.6] vs 89.8g/m 2, 95% CI [83.2, 96.4], p=<0.05). Patients with ICD (n=20) were followed up for 52.6 months±5.8 months. One patient with ICD 1* had VA detected after 7 months of ICD insertion and treated successfully with 1 anti-tachycardia pacing algorithm. Conclusion: The detection of HCM through use of MRI allows for earlier diagnosis of patients and provides for accurate and reproducible measurements of LVwt and LVIBSA x as opposed to TTE. In our retrospective study it is suggested that higher LVIBSA is related to increase incidence of VA. If LVIBSA derived from MRI were applied to ESC guidelines, this could result in more patients ICD 1* . We feel this should be explored with larger studies to see if LVIBSA is an independent risk factor for SCD.